Aislamiento de bacterias patógenas al humano en cultivos agrícolas de la cuenca del río Chambo. - María Guadalupe, Guamán Chabla (2019)
Currently, antimicrobial resistance has become one of the most significant difficulties in terms of antibiotic treatment, due to the evolution of the microorganisms most likely to proliferate in various environments. The purpose of this study is to determine the antimicrobial resistance of isolated pathogenic bacteria in crops in the Chambo river basin, which shows the existence of multiresistant pathogens, being the leading cause of infections in the gastrointestinal tract in the agricultural population. The research is descriptive, presents a cross-sectional field and cohort design. The collection of crops distributed in six geographical points was executed; for the microbiological analysis, it was necessary to measure the ambient temperature and altitude. For bacterial isolation and identification, Blood agar, McConkey, and CLED were used, together with biochemical and physiological tests to classify bacteria by gender and species. The colony isolation technique measured susceptibility and antimicrobial resistance and using the Kirby-Bauer method. The acquired results show the presence of 6 bacteria of clinical interest: 5 gram-negative, enterobacteria (83.3%) among them: Citrobacter freundii, Citrobacter amalonaticus, Enterobacter cloacae, Proteus Vulgaris, Klebsiella oxytoca and only one gram-positive (16.7%): Enterococcus faecalis respectively. The majority of the bacteria showed resistance to 3rd generation carbapenems and cephalosporins, showing the inducible AmpC beta-lactamase mechanism, to a lesser extent, resistance against 2nd generation cephalosporins, penicillin, and glycopeptides. Finally, it follows that the Chambo River is contaminated by bacteria that are resistant